Factors affecting Agrarian Distress Proneness in Western Vidarbha - N.M.Kale,; P.P. Wankhade,; Gopal Jadhao, (Journal of Agricultural Extension Management, 2025)
The present investigation was undertaken in 2008-09 to assess the factors affecting agrarian distress in districts of Western Vidarbha. A sample of 150 small and marginal farmers was selected for the study. The study revealed that, a majority (79.35%) of the respondents were under severe agrarian distress due to effect of weather and yield uncertainties, non remunerative prices, rise in cost of inputs,· 1ack of irrigation facilities, limited availability of credit, rise in indebtedness, supplier induced demand in the market and increasing dependency on others in the farming business. Policy makers need to take care of these triggers/factors for reducing present agrarian distress in selected districts of Western Vidarbha region of Maharashtra.